I Take Refuge in the Sangha. But how? The Puzzle of Intersubjectivity in Buddhist Philosophy Comments on Tzohar, Prueitt, and Kachru - Garfield, Jay L. (Sophia, 2019)
This is a reply to the essays by Catherin Prueitt, Sonam Kachru, and Roy Tzohar on the problem of intersubjectivity in Yogācāra, from a panel at the American Academy of Religion. I argue that the problem of explaining genuine intersubjectivity, as opposed to parallel subjectivity remains unsolved.